Tumour-derived exosomal miR-205 promotes ovarian cancer cell progression through M2 macrophage polarization via the PI3K/Akt/mTOR pathway - Liuqing He; Quan Chen; Xiaoying Wu (Journal of Ovarian Research)
Abstract Background Tumour-associated macrophages (TAMs) are the most abundant immune cells in the tumour environment and are considered similar to M2 macrophages, which facilitate cancer progression. Exosomes, as important mediators of the cross-talk between tumour cells and tumour-associated macrophages, can facilitate the development and metastasis of ovarian cancer by mediating M2 macrophage polarization. However, the exact mechanisms underlying the communication between ovarian cancer (OC) cells and tumour-associated macrophages during OC progression remain unclear. Results Here, we demonstrated that high expression of miR-205 was associated with M2 macrophage infiltration, which affected the prognosis of OC patients. Importantly, tumour-derived miR-205 could be transported from OC cells to macrophages via exosomes and promote cancer cell invasion and metastasis by inducing M2-like macrophage polarization. Animal experiments further confirmed that exosomal miR-205-induced M2 macrophages accelerated OC progression in vivo. Mechanistically, miR-205 downregulated PTEN, activating the PI3K/AKT/mTOR signalling pathway, which is critical for M2 polarization. Conclusions These results reveal that exosomal miR-205 plays a pivotal role in macrophage polarization within the OC microenvironment, highlighting its potential as a therapeutic target for OC treatment. This study not only enhances our understanding of the interactions between tumour and immune cells but also opens new avenues for targeted therapies against exosomal miR-205 in ovarian cancer.